New Rights and the Space of Practices: Italian Contributions to a Theory of the Urban Commons - Michele Vianello (Footprint)
This paper conducts an analysis of two relevant aspects emerging from Italian research on the commons. The first focuses on legal aspects and juridical problems related to the commons, while the second considers practices that enable the collective social reproduction of contemporary urban commons. These two aspects are presented in their theoretical and discursive evolution in relation to their specificity in the Italian context. What is revealed is that they prove to be mutually reliant, and that, when combined, they offer heuristically fruitful perspectives for the advancement of the idea of commons today. A particular emphasis is placed on the difference between customs and practices, the former being the base for traditional arrangements of commoning, the latter being the potential principle for new types of arrangements today. Some specific Italian situations are invoked to illustrate the points made and to provide elements for an analytical approach relevant to different contexts.